Sustained Release of Nanoformulation of Diethyl Carbamazine (Dec) for Filariasis – a Review - Yuvaraj, D; Jai Preethi, P; Saravanan, A; H. Smila, K (International Journal of Engineering and Technology, 2018)
Lymphatic filariasis (LF), is a mosquito vector-borne disease and a major public health problem in the tropical countries. The annual mass drug administration (MDA) in India was studied in 1996-97. It was introduced with single dose of Diethylcarbamazine and was investigated Â as a pilot project covering 41millon population. The study was extended to 77million population by 2002. The MDA is one of the strategies to eliminate LF in India. Liposomes, polymeric and solid lipid nanoparticles are the most promising nanopharmaceuticals which are easy to formulate, cheaper and can bring prolific consequences for filariasis management.Â Â